Pandangan Tengku Gampong tentang Wali Fasik dalam Pernikahan: Studi Kasus di KUA Kecamatan Blangpidie, Abdya (Tengku Gampong's View on Fascical Guardians in Marriage: Case Study in KUA Blangpidie Subdistrict, Abdya Regency) - Misran, Misran; Murdiana, Dian (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
In marry children women, wali (guardian) not be wicked and the majority of scholars requires guardian should fair. However, in community still found practice guardian marriage wicked, especially in district Blangpidie, district Abdya. Thera are three questions research in research this article, first, how procedure wedding at kua district Blangpidie, district Abdya, second, how view tengku gampong district Blangpidie about guardian wicked in wedding, third, what reason dan evidence law that used tengku gampongs and the  KUA. to answer problem in tihis research, it will be done with approach case study. The data collected through observation dan interview. Data research analyzed an qualitative with method deskritif-analysis. Results research show first, implementation wedding at kua district Blangpidie done with five procedure, i.e; preparation marriage notice will marriage examination file marriage announcement will marriage implementation contract marriage good at kua or in out KUA. second, did tengku gampong district Blangpidie, the person who wicked like not implement prayer five time, gamble dan drunkenness be be guardian in wedding. Guardian marriage not obeyed fair, which is important is religious Islam puberty dan rational. third, reason dan evidence law that used tengku gampong and the KUA district Blangpidie in set law guardian wicked in wedding have two, i.e; opinion scholars jurisprudence that allow guardian the marriage wicked marry children, not of rules that firmly in regulations legislation about terms guardian should fair dan not wicked. did tengku gampongs and the KUA district Blangpidie, law marriage dan compilation law Islam only requires guardian should religious Islam aqeel dan puberty.